Chronic Δ(9)-Tetrahydrocannabinol During Adolescence Increases Sensitivity to Subsequent Cannabinoid Effects in Delayed Nonmatch-to-Position in Rats - Wiley, Jenny L. (2009)
Early-onset marijuana use has been associated with short- and long-term deficits in cognitive processing. In human users, self-selection bias prevents determination of the extent to which these effects result only from drug use. This study examined the long-term effects of Δ(9)-tetrahydrocannabinol (Δ(9)-THC), the major psychoactive constituent of marijuana, in a delayed nonmatch-to-position task (DNMP). Male Long-Evans rats were injected daily with 10 mg/kg Δ(9)-THC during or after adolescence [postnatal days (PN) 21-50 or PN50-79, respectively] or with vehicle. On PN91, training in DNMP was initiated. Successful acquisition and pharmacological challenge began on approximately PN300. Decreases in accuracy were observed at lower doses of Δ(9)-THC in Δ(9)-THC-treated rats (versus vehicle-treated rats). Administration of chronic Δ(9)-THC at a younger age tended to enhance this effect. While anandamide did not decrease accuracy in any group, rats treated with Δ(9)-THC during adolescence initiated fewer trials at the 30 mg/kg dose of anandamide than did rats in the other two groups. To the extent tested, these differences were pharmacologically selective for cannabinoids, as scopolamine (positive control) decreased accuracy at the same dose in all groups and amphetamine (negative control) did not affect accuracy in any of the groups at doses that did not impair overall responding. These results suggest that repeated administration of a modest dose of Δ(9)-THC during adolescence (PN21-50) or shortly thereafter (PN50-79) produces a long-term increase in latent sensitivity to cannabinoid-induced impairment of performance in a complex operant task.